EVALUATION OF THE DETERMINATION AND IMPLEMENTATION OF BEYOND-USE DATE (BUD) TO NON-STERILE EXTEMPORANEOUS COMPOUNDED MEDICINES BY PHARMACISTS IN SUKOHARJO INDONESIA - KARUNIAWATI, HIDAYAH; HI, MARSILIA ROSA SINENSIS (International Journal of Applied Pharmaceutics, 2024)
Objective: This research aims to evaluate pharmacists' determination and implementation of Beyond-Use Date (BUD) for extemporaneously compounded medicines from non-sterile drugs and the factors that influence it. Methods: This research is a non-experimental cross-sectional study that used a validated questionnaire with the cluster sampling method applied to select pharmacists. The data were analyzed statistically using the Mann-Whitney, Kruskal Wallis tests and Spearman Correlation. Results: Of the 181 pharmacists who participated, 161 (89.0%) were aged 26–45 years, 160 (88.4%) were women, 118 (65.2%) were married, and 173 (95.6%) had a bachelor's degree with a profession. Around 75%–77% of respondents calculate BUD on the extemporaneous compounded and mark BUD on the drug label or medicine packaging. Around 80% of pharmacists inform patients about BUD, but only 65% ensure patients understand it. Age, marital status, education level, length of work experience, and income significantly influence the determination and implementation of BUD (P<0.05). Knowledge has a significant relationship with pharmacists' attitudes (r = 0.836) and behavior (r = 0.646) towards BUD Conclusion: The role of pharmacists in determining and implementing BUD in extemporaneously compounded medicines needs to be improved to ensure maximum drug quality, safety, and optimal therapy.